2011
DOI: 10.1002/jor.21404
|View full text |Cite
|
Sign up to set email alerts
|

Early joint tissue changes are highly correlated with a set of inflammatory and degradative synovial biomarkers after ACL autograft and its sham surgery in an ovine model

Abstract: While impossible in humans, the mechanisms of early cartilage, bone and meniscal damage can be quantified after anterior cruciate ligament (ACL) injury in animal models. We utilized an ovine model to determine if the mRNA expression of inflammatory and degradative molecules (IL-1b, IL-6, MMP-1, 2, 3, and 13) in the synovium correlated to changes in joint tissues 2 weeks post-ACL surgery, to test the hypothesis that synovial inflammation is a marker of these changes and possibly their originator. Nine ''idealiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 26 publications
(27 reference statements)
5
55
1
Order By: Relevance
“…Interestingly, in the present study we observed that both the synovium and the cartilage tissue from the femoral condyle and the tibial plateau region exhibited concurrent expression of inflammatory markers. Such results clearly show that injection of carrageenan in the joint environment has an influence on both the cartilage and the synovium, similar to the previous reports on ACL autograft model studies [36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in the present study we observed that both the synovium and the cartilage tissue from the femoral condyle and the tibial plateau region exhibited concurrent expression of inflammatory markers. Such results clearly show that injection of carrageenan in the joint environment has an influence on both the cartilage and the synovium, similar to the previous reports on ACL autograft model studies [36].…”
Section: Discussionsupporting
confidence: 91%
“…The results presented in this report indicate that a single injection of carrageenan into the rabbit knee leads to the elevated expression of MMPs and cytokines, not unlike that previously observed following an ACL injury and early OA development [34][35][36]. In the present study, the inflammatory response in synovial tissue peaked at 2 weeks post-carrageenan treatment, as exhibited by significant elevation in mRNA levels for IL-1b and IL-6.…”
Section: Discussionsupporting
confidence: 59%
“…abortus infection inhibits apoptosis induced by supernatants from B. abortus-infected monocytes and neutrophils. Neutrophils and monocytes have been shown to induce apoptosis of cells from infiltrated tissues due to the release of MMPs, reactive oxygen species, and TNF-␣ (34,44,45). However, our results indicate that B. abortus infection inhibits apoptosis of synoviocytes induced by STS.…”
Section: Neutrophils and Monocytes Adhere To B Abortus-infected Synocontrasting
confidence: 58%
“…However, other possibilities likely also exist. In studies of partial injuries to the ACL in either rabbit (Lo et al, in preparation; Heubner et al, in preparation) or sheep models (Heard et al, 2011), the response to injury leads to an inflammation. In fact, a partial injury to one band of the ACL leads to an initial response not dissimilar to that of the MCL at 3 weeks post-injury, which then fails to mature and ultimately fails to lead to functional repair, possibly due to persistent inflammation (Lo et al, in preparation).…”
Section: Compromised Healing Of the Injured Aclmentioning
confidence: 99%